Design and evaluation of novel bio‐based deep eutectic solvents for highly efficient bioproduction of chiral aryl alcohol. Issue 7 (13th March 2020) - He, Yushu; Huang, Qianyue; Wang, Pu
Abstract: BACKGROUND: Deep eutectic solvents (DESs) derived from bio‐available materials are promising eco‐friendly solvents in the field of biocatalysis. However, the type of bio‐based DES is still limited and its application in bioprocess has not been well‐explored. We adopted a design strategy via the combination of choline and amino acids to synthesize novel bio‐based DESs, aimed to enhance biocatalytic efficacy by exploiting the developed DESs as co‐solvents. RESULTS: Various bio‐based DESs were synthesized, where the two components are both bio‐available (choline and amino acids). Their performances in the bioreduction of 2‐chloro‐1‐(3, 4‐difluorophenyl)ethanone (CFPO) were subsequently evaluated with recombinant Escherichia coli cells. The efficient asymmetric production of ( S )‐2‐chloro‐1‐(3, 4‐difluorophenyl)ethanol (( S )‐CFPL) was successfully achieved in a developed choline acetate/lysine (ChAc/Lys)‐containing medium. ChAc/Lys can strengthen coenzyme regeneration and properly improve cell membrane permeability during bioreduction, which account for high conversion. After optimized reaction parameters were conducted in the ChAc/Lys‐buffer system, 87.0% ( S )‐CFPL yield was observed with > 99.9% enantiomeric excess (ee) value at 1 mol L −1 CFPO content. The substrate loading in the established ChAc/Lys‐buffer system was increased by 3.3‐fold compared to aqueous medium. This bioprocess was also proved to be feasible at 500 mL preparative‐scale with a satisfactory conversion. CONCLUSION: ChAc/Lys bio‐DES is a promising and biocompatible co‐solvent. Introducing ChAc/Lys to the reaction system is an effective strategy for challenging high substrate loading for bioreduction. Our results give a valuable insight for developing green and benign sustainable bio‐DESs for biotransformation. © 2020 Society of Chemical Industry